The concept of bilinguvism in the categorial field of the theory and methodology of professional education - Ситняківська, С. М. (Scientific notes of the pedagogical department, 2019)
Our country is on the way to European integration. That is why modernization takes place in all spheres of life, including the educational sphere. Today, there are changes in the content of education, it acquires a multicultural character. In this regard, learning a foreign language or bilingual education becomes an integral part of the process of forming a modern specialist. However, despite the prolonged presence of the concept of bilingualism in the world’s theory and practice of teaching, today there is the problem of the conceptual apparatus of the theory of bilingual education. Different scholars interpret the notion of «bilingualism» differently, depending on the linguistic, psychological, sociological, culturological, methodological angle of the characteristic and analysis of this concept. Therefore, the problem of content analysis and definition of the concept of bilingualism and its derivative concepts in the system of professional training of specialists in higher educational institutions of Ukraine appears. The article analyzes the concept of bilingualism from the point of view of the theory and methodology of professional education. The essence of the concepts of «bilingual education» and «bilingual teaching» was determined based on the analysis and characterization of the concept of «bilingualism». Under bilingual education in the system of future specialists’ professional training we suggest understanding the process of training, in which special (professional) subjects are taught in a foreign language. Under bilingual education it is proposed to understand the interrelated activities of the teacher and students in the process of studying some subjects in the specialty by means of a foreign language, as a result of which a high level of competence is achieved, which ensures a high level of proficiency in a foreign language and deep learning of the subject matter of the professional (special) subjects. It was proved that the development of the theory and practice of bilingual education and teaching in national higher educational institutions is an attempt to create a new educational standard, the emergence of which is dictated by the objective conditions of the development of foreign language education, on the one hand, and integration processes in the world, on the other.